The Impact of Marine Plastic Pollution in Asia-Pacific on Small-Scale Fisher’s Rights - Ayodya Maheswara, Ida Bagus (Serikat Pengajar Hak Asasi Manusia Indonesia, 2023)
This paper examines the impact of marine plastic pollution on small-scale fishers in Asia-Pacific countries and how the existing international law accommodates this problem. The research method used is doctrinal legal research with a statute approach and case approach using primary, secondary, and tertiary legal materials analysed with descriptive analytical techniques. The results show that Asia-Pacific is the most significant contributor to marine plastic pollution in the world as a region at the centre of the world's economic growth. The fisheries industry is one of the economic sectors that is the mainstay of countries in the Asia-Pacific, such as Indonesia, Australia, and China, because it contributes to a high Gross Domestic Product and becomes a job for small-scale fishers. However, marine plastic pollution is a problem because it contaminates fish, impacting fishermen's productivity. This has eliminated the rights of fishermen, especially the small-scale fisher, to obtain decent work and the right to an adequate standard of living. Meanwhile, the existing international law has yet to accommodate the plastic waste problem in the Asia-Pacific Ocean explicitly, so there is legal uncertainty that regulates this problem. This research concluded that the issue of marine plastic pollution in the Asia-Pacific must be handled seriously by formulating an agreement between countries in the region that contains more technical and specific arrangements to maintain the rights of small-scale fishers in obtaining decent work and adequate living standards.